2020
DOI: 10.1186/s13058-020-01278-7
|View full text |Cite
|
Sign up to set email alerts
|

ERα-36 regulates progesterone receptor activity in breast cancer

Abstract: Background: Alterations in estrogen and progesterone signaling, via their respective receptors, estrogen receptor alpha (ERα) and progesterone receptor (PR), respectively, are largely involved in the development of breast cancer (BC). The recent identification of ERα-36, a splice variant of ERα, has uncovered a new facet of this pathology. Although ERα-36 expression is associated with poor prognosis, metastasis development, and resistance to treatment, its predictive value has so far not been associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…However, in another Chinese patient cohort with ER-negative breast cancer, ERα36 was not found to have any correlation with clinicopathological characteristics, and its inhibition in breast cancer cell lines was reported to increase their sensitivity to paclitaxel [ 51 ]; however, membrane/submembrane expression was not examined separately in this study. A recent study also reports the direct interaction of ERα36 with PR, with the first one inducing the expression of the latter and thus affecting its activity in a manner that increases the aggressiveness of breast cancer cells and leading to poorer patient prognosis [ 13 ]. However, in the last study, all PR-positive patients were also ERα66-positive, complicating the interpretation of these findings, while an unexpected better prognosis of PR-negative patients expressing high levels of ERα36 was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in another Chinese patient cohort with ER-negative breast cancer, ERα36 was not found to have any correlation with clinicopathological characteristics, and its inhibition in breast cancer cell lines was reported to increase their sensitivity to paclitaxel [ 51 ]; however, membrane/submembrane expression was not examined separately in this study. A recent study also reports the direct interaction of ERα36 with PR, with the first one inducing the expression of the latter and thus affecting its activity in a manner that increases the aggressiveness of breast cancer cells and leading to poorer patient prognosis [ 13 ]. However, in the last study, all PR-positive patients were also ERα66-positive, complicating the interpretation of these findings, while an unexpected better prognosis of PR-negative patients expressing high levels of ERα36 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Deriving from an alternative transcriptional initiation at the first intron, it contains exons 2–6 of the classic ERα and a unique 27-amino acid C′-terminal sequence, thus missing transcriptional activation domain AF1 and part of AF2, but retaining the DNA-binding domain, the dimerization capacity, and most of the sequence of ERα66 critical for ligand binding [ 6 ]. We have previously reported that ERα36 is expressed in breast cancer cell lines and in the cancer tissues of a cohort with triple-negative breast cancer (TNBC) patients, where its membrane localization is a good prognostic indicator [ 11 ], although controversial results regarding the clinical significance of this isoform exist [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study confirmed that the expression of ERα36 was of poor prognosis in PR-positive tumors. However, this expression was significantly associated with longer survival in PR-negative tumors, suggesting a crosstalk between ERα36 and PR in breast cancer [55]. Therefore, ERα36 could become a new prognostic marker to discriminate a subset of PR tumors, generally associated with a good prognosis that may develop metastases.…”
Section: The Prognostic Value Of Erα36mentioning
confidence: 99%
“…However, so far, ERα36 has been shown to regulate only ERα activity [11]. Recently, Konan and colleagues [55], showed that ERα36 binds to progesterone receptor (PR) and interferes with progesterone signaling. Indeed, ERα36 modulates PR expression, phosphorylation, and transcriptional activity.…”
Section: Era36 and Other Hormonal Nuclear Receptors?mentioning
confidence: 99%
See 1 more Smart Citation